Chewing-stick practices using plants with anti-streptococcal activity in a Ugandan rural community - Charles Okot Odongo; Charles Okot Odongo; Nathan Lubowa Musisi; Paul eWaako; Celestino eObua (Frontiers Media S.A., 2011)
Background: The high dental disease burden in developing countries has created a need to explore and develop cheap and accessible methods of dental disease prevention. Traditional toothbrushes (chewing-sticks) prepared from specific plants have been used for dental hygiene for generations. When properly used, chewing sticks may be as effective as synthetic toothbrushes. This study set out to describe traditional chewing-stick practices in a Ugandan rural community, and evaluate the antibacterial activity of two most commonly used plants. Methods: Interviews were done to identify chewing-stick plants and obtain socio-cultural information relating to the practice in two villages in rural Uganda. Field walks were done to pick and voucher the plants, for taxonomical identification and storage. For the two most reported plants, aqueous extracts were prepared and tested for antibacterial activity against Streptococcus mutans using the agar-well diffusion method. Results: Of the 21 key informants interviewed, all were using or had used chewing sticks in the past. A total of eight plants were identified as sources of chewing sticks, with Rhus vulgaris and Lantana trifolia most commonly mentioned. Chewing sticks were preferred over synthetic tooth brushes because they were less likely to traumatize the gums. Their use has been limited of recent due to scarcity of some plants. Rhus vulgaris and Lantana trifolia aqueous extracts showed antibacterial activity against Streptococcus mutans with mean diameters of inhibition of 24.33 ± 0.58 mm and 14.17 ± 0.29 mm on Blood agar respectively, compared to benzyl penicillin control 30.67 ± 0.29 mm. Conclusions: Rhus vulgaris and Lantana trifolia are the most common sources of chewing sticks for cleaning teeth in this community. The plants contain compounds that are active against Streptococcus mutans. These plants merit further studies as they are possible sources of cheap dental health care for the rural poor.